2009
DOI: 10.1152/ajpcell.00597.2008
|View full text |Cite
|
Sign up to set email alerts
|

Titanium particles stimulate COX-2 expression in synovial fibroblasts through an oxidative stress-induced, calpain-dependent, NF-κB pathway

Abstract: In prosthetic loosening, bone resorption is induced by wear debris particles generated from the artificial joint articulation. Our prior work showed that synovial-like fibroblasts respond to titanium particles by producing receptor activator of NF-kappaB ligand (RANKL), a critical activator of osteoclastogenesis. While this effect occurs through a cyclooxygenase-2 (COX-2)-dependent pathway, the mechanism of COX-2 stimulation by titanium particles is not clear. Here we show that titanium particles induce COX-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 59 publications
(91 reference statements)
1
18
0
Order By: Relevance
“…It was reported that NF-κB up-regulated TNF-α and IL-1β expression by monocytes32. Meanwhile, previous studies demonstrated that NF-κB pathway was activated by wear particles and subsequently promoted pro-inflammatory cytokines expression933. In addition, blockade NF-κB activity results in a significant reduction in pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 98%
“…It was reported that NF-κB up-regulated TNF-α and IL-1β expression by monocytes32. Meanwhile, previous studies demonstrated that NF-κB pathway was activated by wear particles and subsequently promoted pro-inflammatory cytokines expression933. In addition, blockade NF-κB activity results in a significant reduction in pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 98%
“…As for the ethanol-treated particles, the activation of NF-jB nuclear translocation and the production of proinflammatory cytokines are significantly greater than in the other groups when more endotoxins present on the particles. This observation is the reason that many studies have indicated that the wear particles could activate NF-jB nuclear translocation even when all particle preparations were shown to be free of endotoxin by LAL-based assay in their studies [33][34][35]. However, another paper also demonstrated that titanium-alloy particles without endotoxin did not induce NF-jB activation [36].…”
Section: Discussionmentioning
confidence: 99%
“…These results have minimized the influence of endotoxins on the particles because all particle preparations were shown to be free of endotoxin by LAL-based assay [33][34][35].However, other research has also demonstrated that the titanium-alloy particles without endotoxins did not induce NF-jB activation [36]. To examine NF-jB activation, RAW264.7 cells that were stably transfected with a luciferase reporter gene p-NF-jB-TA-Luc [37] were plated in 24-well plates at a density of 1 9 10 5 cells/well and treated with three groups of particles for 8 h. The cells were harvested, and the luciferase activity was measured using the Promega Luciferase Assay System according the manufacturer's instructions (Promega).…”
Section: Nf-jb Luciferase Reporter Gene Assaymentioning
confidence: 99%
“…Cells were incubated with trypsin (0.25%), collected, diluted (1:4) with trypan blue, and examined by microscopy. Viability was assessed by the fraction of cells that excluded the dye, as previously reported (Wei et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…These findings were subsequently extended to show that bilirubin reacts with other reactive oxygen and nitrogen species including hypochlorous acid, singlet oxygen, hydroxyl radical, nitric oxide, and peroxynitrite (see Stocker, 2004). Indeed, numerous studies have demonstrated a cytoprotective role for bilirubin in response to various oxidative insults (Yamaguchi et al, 1996; Clark et al, 2000; Dore et al, 2009; Wei et al, 2009; Jansen et al, 2010). In addition, bilirubin exerts critical anti-inflammatory actions in the vasculature.…”
Section: Introductionmentioning
confidence: 99%